Neuroprotective Effects of the Ethanolic Leaf Extract of Crassocephalum crepidioides (Asteracaeae) on Diazepam-Induced Amnesia in Mice - Beppe Galba Jean; Folefack Alice Irène; Atsamo Albert Donatien; Ngatanko Aïbassou Hervé-Hervé; Barga Mpoo Bertrand; Allah-Doum Nanou Gael; Nguedia Ymele Merline; Zemo Gamo Franklik; Dongmo Alain Bertrand; Dimo Théophile (Advances in Pharmacological and Pharmaceutical Sciences)
This study aimed to evaluate the neuroprotective effects of the ethanolic leaf extract of Crassocephalum crepidioides (Cc) on diazepam-induced amnesia in mice. Thirty mice distributed into six groups of five mice each were used. The normal control and negative control groups received 2% ethanol per os, the positive control group received piracetam (150 mg/kg, p.o), and three experimental groups were treated with three doses of ethanolic leaf extract of Cc (100, 200, and 400 mg/kg, p.o). All groups except the normal control group were co-treated with diazepam (3 mg/kg, i.p) daily for 14 days. The memory effects were evaluated using the Radial Arm Maze (RAM) and the Novel Object Recognition (NOR) tests, while the anti-depressive effects were evaluated using the tail suspension test. All animals were sacrificed at the end of the study. Hippocampi, isolated from the right hemisphere, were used to prepare a homogenate for the determination of oxidative stress biomarkers. The ethanolic leaf extract of cc significantly (p<0.001) decreased the number of working and reference memory errors in the RAM test and induced a significant (p<0.01) increase in the time spent exploring the novel object in the NOR test. The extract also induced a significant (p<0.001) increase in the mobility time in tail suspension. Moreover, compared to the negative control group, the extract significantly (p<0.01) increased superoxide dismutase activity and significantly (p<0.01) decreased malondialdehyde levels. The histopathological analysis of hippocampi showed that the cc extract increased cell density when compared with the negative control. These results suggest that the ethanolic left extract of cc could have neuroprotective properties, which could be attributed to its antioxidant properties.